Obustronny zespół Adiego u dziecka - Gotz-Więckowska, Anna; Kocięcki, Jarosław (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Bilateral Adie’s syndrome is characterized by the presence of a tonic pupil connected with accommodation problems. Very often, it coexists with latent hypermetropia, corneal hyposensivity. Typical signs are weakened tendons reflexes. We present the 8 years old girl with bilateral Adie’s syndrome, which was the cause of school problems.